2002
DOI: 10.1111/0022-1082.00495
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Informational Role of Short Interest in the Nasdaq Market

Abstract: This paper examines the relationship between the level of short interest and stock returns in the Nasdaq market from June 1988 through December 1994. We find that heavily shorted firms experience significant negative abnormal returns ranging from Ϫ0.76 to Ϫ1.13 percent per month after controlling for the market, size, book-to-market, and momentum factors. These negative returns increase with the level of short interest, indicating that a higher level of short interest is a stronger bearish signal. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
323
5
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(349 citation statements)
references
References 23 publications
18
323
5
3
Order By: Relevance
“…Diamond and Verrecchia (1987) propose that unanticipated increases in short selling will be followed by a price decline. Consistent with the proposition of Diamond and Verrecchia, Senchack and Starks (1993) and Desai et al (2002) show that monthly short interest predicts negative returns for NYSE stocks and NASDAQ stocks, respectively.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Diamond and Verrecchia (1987) propose that unanticipated increases in short selling will be followed by a price decline. Consistent with the proposition of Diamond and Verrecchia, Senchack and Starks (1993) and Desai et al (2002) show that monthly short interest predicts negative returns for NYSE stocks and NASDAQ stocks, respectively.…”
Section: Introductionsupporting
confidence: 62%
“…Research showing that short sellers are informed about future stock returns is robust (Diamond and Verrecchia, 1987;Senchack and Starks, 1993;Aitken et al, 1998;Desai et al, 2002;Christophe, Ferri, and Angel, 2004;and Boehmer, Jones, and Zhang, 2008). Diether, Lee, and Werner (2009) argue that informed investors are able to short stocks that become overvalued or out of line with their fundamental value while documenting the short sellers are contrarian in contemporaneous and past returns.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have used monthly stock-specific short interest data (e.g., Figlewski and Webb (1993), Figlewski (1981), Dechow, Hutton, Meulbroek, and Sloan (2001), Desai et al (2002), Asquith, Pathak, and Ritter (2005), and Singal and Xu (2005)). There are three important problems with using monthly short interest data.…”
Section: Introductionmentioning
confidence: 99%
“…We estimate the 13) To eliminate the reverse causality effect, we defined the DTS industry based on the ranks of previous quarter. 14) Figlewski (1981) and Desai et al (2002) showed that a high fraction of shares shorted precedes low future returns.…”
Section: Empirical Analysismentioning
confidence: 99%